Entrepreneurial Intentions of Students Using The Shapero Entrepreneurial Event Model - Indarwati, Yuniar Riska; Syahran, Syahran (LPPM of NAROTAMA UNIVERSITY, 2024)
Objective: This research aims to examine the influence of entrepreneurship education, self-efficacy, and perceived desire on entrepreneurial intentions using the Shapero Entrepreneurial Event Model theoretical approach. Design/ methodology/ approach The population in this study was 280 Tarakan City students. The data used in this case. This research is primary data sourced from questionnaires. This research uses a quantitative approach with survey methods. Variable measurement uses a Likert scale and the sampling technique used is non-probability sampling with a purposive sampling method. The analysis technique used is SEM (Structural Equation Modeling) with SPSS and LISREL 8.80 software tools. Findings: The findings show that entrepreneurship education has a positive and significant effect on self-efficacy, self-efficacy has a positive and significant effect on entrepreneurial intentions, and perceived desire has a positive and significant effect on entrepreneurial intentions. Paper type: Research paper